Subauroral Green STEVE Arcs: Evidence for Low‐Energy Excitation. Issue 24 (23rd December 2019) - Mende, S. B.; Harding, B. J.; Turner, C.
Abstract: Subauroral emissions known as STEVEs (Strong Thermal Emission Velocity Enhancements) are sometimes accompanied by green arcs containing magnetic field‐aligned "picket fence" structures. In a newly published spectrum of a green picket fence arc Gillies et al. (2019, https://doi.org/10.1029/2019GL083272 ) showed that the visible emission in such arcs is mostly OI 557.7 nm with minimal N2 + 1N. This finding is consistent with the color ratios found in digital camera photos (Mende & Turner, 2019, https://doi.org/10.1029/2019JA026851 ) and is distinct from the ratios in auroral precipitation. The spectrum also contains intense N2 first positive (1P) emission. The presence of OI 557.7 ( 4.19 eV excitation energy) and N2 1P ( 7.35 eV), combined with the lack of N2 + first negative ( 18.75 eV) commonly seen in the aurora, suggests that the particles exciting the emission have energy <18.75 eV. This is strong evidence against the precipitation hypothesis recently put forth (Nishimura et al., 2019, https://doi.org/10.1029/2019GL082460 ; Gillies et al., 2019, https://doi.org/10.1029/2019GL083272 ). Key Points: Recent spectra of a green STEVE arc shows intense 557.7 nm OI and N2 1P nitrogen emission in the IR but minimal N2 + 1N in the blue Color ratios in photos of the green "picket fence" arcs are consistent with the spectrospcopic results Spectra and the color ratios show low energy excitation which is inconsistent with auroral source from the magnetosphere